Colour theory. - Yoon, Davier Wai Cheong. (2010)
COLOUR THEORY is a story about how a young scientist, in a black and white world, has found a way to view colour, after experimenting with some chemicals. His discovery, however, becomes a nightmare when he finds out that his face is permanently disfigured by the chemicals he used. The disfigurement causes parts of his face to change hue, but maintain lightness, it can only be seen in colour. Through this simple story, I hope to explore the implications of knowing more than we can handle.